Kritik atas Kerancuan Pemahaman terhadap Istilah Takdir dan Sunatullah dalam Konteks Bencana Alam - Ahmad Husnul Hakim (Refleksi, 2021)
This article is based on the ambiguous understanding of the terms destiny and sunatullah in the context of natural disasters. Where natural disasters are something that is commonplace for every human being. Because, every human being must have experienced, seen, or heard news about natural disasters. However, people's responses have always been different, at least in three views. First, they assume that natural disasters are merely natural occurrences. Second, they assume that natural disasters are the result of human behavior. Third, they think it is part of God's destiny and will. In relation to these three views, further criticism is needed so that there is no confusion of understanding. The question of natural disasters is destiny or sunnatullah? Some of these views certainly have consequences. This is the issue that will be discussed in this article. This research model is a qualitative research based on literature study. Meanwhile, the verses will be discussed using the thematic interpretation method.